RANCANG BANGUN ALAT PENYULING DAUN SERAI MENGGUNAKAN METODE STEAM HYDRODISTILLATION - Didik Sugiyanto; Yefri Chan; Fahmi Aldi; Hernando Christian (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
This study aims to design and test the citronella leaf distillation tool by conducting experiments and testing the tools and test results. The parameters observed were heat transfer in the citronella leaf distillery produced by the tool, the results of the conduction heat transfer research in the distillation tank were 1,032.61 J/s (Joules per second) and heat transfer by natural convection in the distillation tank was 3,761.16 J/s (Joules per second) with an initial water temperature of 28°C to a specified temperature of 98°C. The distillation time of more than 5 hours will reduce the quality of the yield which is not up to standard. The effect of the part of lemongrass which produces a high yield percentage is on the leaves, while the high quality of citronella oil is on the leaves. % citronella citronella on fresh leaves was 67.36%, withered leaves were 44.92%.